11-3x=44
One solution was found :
x = -11
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
11-3*x-(44)=0
Step by step solution :
Step 1 :
Pulling out like terms :
1.1 Pull out like factors :
-33 - 3x = -3 • (x + 11)
Equation at the end of step 1 :
Step 2 :
Equations which are never true :
2.1 Solve : -3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
2.2 Solve : x+11 = 0
Subtract 11 from both sides of the equation :
x = -11
One solution was found :
x = -11
Processing ends successfully